1999
DOI: 10.1093/ajcp/112.3.366
|View full text |Cite
|
Sign up to set email alerts
|

BsmlPolymorphism of the Vitamin D Receptor Gene in Hyperparathyroid or Hypoparathyroid Dialysis Patients

Abstract: A b s t r a c t Since bone mineral density may be influenced by the polymorphisms of the vitamin D receptor (VDR JgeneBone mineral density is influenced by environmental factors, such as dietary calcium intake and physical activity, and by genetic determinants. Since vitamin D is important in calcium metabolism and bone turnover, it has been suggested that polymorphisms for the vitamin D receptor (VDR) gene may be one of these factors. In a large population of healthy whites, Morrison and coworkers 1 -2 descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Similarly, Tagliabue et al [48], reported a higher frequency of BB variant among Italian dialysis patients with hypoparathyroidism compared to patients with secondary hyperparathyroidism (34% versus 16%). Also, a protective effect of the B allele has been reported in Japanese patients undergoing hemodialysis [49].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Tagliabue et al [48], reported a higher frequency of BB variant among Italian dialysis patients with hypoparathyroidism compared to patients with secondary hyperparathyroidism (34% versus 16%). Also, a protective effect of the B allele has been reported in Japanese patients undergoing hemodialysis [49].…”
Section: Discussionmentioning
confidence: 80%
“…[14] Also in our study the frequency of BB genotype is higher in groups III (300 ≥ iPTH < 600 pg/mL) and IV (iPTH ≥ 600 pg/mL) thus BB genotype may develop more severe secondary hyperparathyroidism but the relationship between BsmI variants and serum iPTH level was not statistically significant. Tagliabue et al .,[15] in their study concluded that patients with the B allele and BB genotype had a significantly lower serum PTH and alkaline phosphatase levels than patients with the b allele and bb genotype but the difference did not reach statistical significance. In our study, the calcium level seen in the BB genotype is less than those for Bb and bb genotypes ( P = 0.002).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, most studies have been aimed at determining whether VDR polymorphisms could be involved in the development of secondary hyperparathyroidism (sHPT), one of the main complications in patients with CKD. Interestingly, the VDR BsmI b allele was shown to have a higher incidence in HD patients with sHPT and drive the progression toward sHPT in patients with ESRD, since BB individuals had lower levels of PTH and higher calcitriol levels than bb individuals in every stage of CKD [13,14,15,16,17]. Serum PTH levels in CKD patients were also affected by FokI polymorphism, since patients in the FF group had significantly higher PTH levels than those in both the Ff and ff groups, while no significant differences in serum levels of calcidiol or calcium were found among genotypes [18].…”
Section: Discussionmentioning
confidence: 99%